An Artificial Intelligence-Driven Framework for Innovation in Legal Decision-Making - Silva Pinto Junior, Joelias; Silvestro, Anderson Ricardo; Faria Culmant Ramos, Vinícius; de Souza, João Artur (Revista Contabilidade & Inovação, 2025)
Objective: To develop a methodology for innovation supported by artificial intelligence for its application in a Regional Labor Court (TRT), with the aim of identifying opportunities for innovation and optimization in decision-making processes in the judicial field. Method: The project, currently under development, originated from a collaboration between a Regional Labor Court and the Federal University of Santa Catarina, with the objective of implementing advanced Information and Communication Technologies (ICT) in judicial offices, to increase efficiency and agility in the routine of magistrates. A systematic literature search was conducted, following the criteria established in the PRISMA guideline. The search was carried out between April and May 2024 and considered articles published from 2018 onwards in English, Portuguese, or Spanish, without geographical restrictions, in the SCOPUS, Web of Science, SciELO, IEEE Xplore, and Google Scholar databases. A total of 614 articles were retrieved, of which, after removing duplicates and applying the inclusion and exclusion criteria, 46 articles were selected for reading, which served as the basis for the project. Main Results: The systematic literature search showed a recent increase in the use of Artificial Intelligence techniques for information retrieval, decision prediction, and decision-making. The search also assisted in the process of choosing the methods and technologies that were selected to compose the innovation methodology supported by applied artificial intelligence proposed by the project and presented here. Main Contributions: We hope that the application of this methodology will result in the development of an innovative and effective tool to assist judges and advisors in their decision-making processes, improving the accuracy and agility of legal processes.